Are Men or Women More Unsettled by Fixed-Term Contracts? Gender Differences in Affective Job Insecurity and the Role of Household Context and Labour Market Positions - Nicolas Morgenroth; Brigitte Schels; Nils Teichler (European Sociological Review, 2022)
This study investigates differences in the causal effect of fixed-term contracts on affective job insecurity by gender and household context in Germany. Research shows that workers in fixed-term employment are more unsettled about their job security than are permanent employees. We contribute to the literature on subjective job insecurity by explicitly modelling the causal effect of fixed-term employment and by examining how women and men differ in this effect. We argue that gender differences in the labour market positions and a gendered division of labour in the household account for gender differences in the subjective vulnerability to fixed-term employment. We apply linear fixed effect probability models based on the German Socio-Economic Panel (SOEP) with a sample of employees aged between 20 and 45 years. Results show that a fixed-term contract doubles the probability of big job worries compared to a permanent contract. Women are substantially more unsettled by fixed-term contracts than men across all household types. These gender differences cannot be explained by unfavourable labour market positions of women. Fixed-term employment thus seems to add to existing gender inequalities on the labour market.
Keywords: 300